Shaking table tests on concrete blocks anchored at the bottom of hydrogen storage vessels considering field installation conditions - Sang-Moon Lee; Young-Jun Bae; Woo-Young Jung (Journal of Asian Architecture and Building Engineering, 2025)
In this study, a scale model was created based on field investigation and design standards to evaluate the structural safety of a vertical hydrogen storage vessel stored in gas and liquid form during an earthquake, and a shaking table test was performed. Through testing, it was recognized that fixed anchors were also vulnerable to earthquakes, and additional seismic performance tests were conducted. In Set 1, where gas was stored, no damaged areas were observed during the maximum input seismic motion (EQ 200 %). In Set 2, where liquid was stored, cracks began to appear between the concrete block and the foundation at EQ 100 %, corresponding to the seismic design standard, and progressed to complete destruction at EQ 150 %. Cracks between the concrete block and the foundation led to a decrease in resonant frequency, accompanied by an amplification in acceleration. A reduction in resonant frequency by more than 15 % is anticipated to result in severe damage to the substructure, indicating a potential for brittle failure due to concrete damage prior to anchor failure. The anchors exhibited residual loads of over 80 % of the design load on average, confirming the use of anchors meeting seismic performance requirements.